Analisis Kualitas Informasi Situs Web Indonesia.go.id sebagai Portal Informasi Indonesia - Putri, Adella Qanita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to provide an overview of the Indonesia.go.id website as an Indonesian information portal from the Ministry of Communication and Information. This research uses qualitative methods, data collection techniques using observation and literature study. This research was analyzed using one of the elements of PAPA, that is Accuracy, and the indicators used as a reference in conducting the analysis were the theory of 20 (twenty) dimensions of information quality from Knight Burn (2005), such as Accuracy, Consistency, Security, Timeliness, Completeness, Concise, Reliability, Accessibility, Availability, Objectivity, Relevancy, Useability, Understandbility, Amount of data Believability, Navigation, Reputation, Useful, Efficiency, and Value Added.